A retinal origin of nystagmus—a perspective - Kamermans, Maarten; Winkelman, Beerend H. J.; Hölzel, M-B.; Howlett, Marcus H. C.; Kamermans, Wouter; Simonsz, H. J.; de Zeeuw, C. I. (Frontiers in Ophthalmology, 2023)
Congenital nystagmus is a condition where the eyes of patients oscillate mostly horizontal with a frequency between 2 and 10 Hz. Historically, nystagmus is believed to be caused by a mal-adaptation of the oculomotor system and is thus a disease of the brain stem. However, we recently showed that congenital nystagmus associated with congenital stationary night blindness is caused by synchronously oscillating retinal ganglion cells. In this perspective we will discuss how some details of nystagmus can be accounted for by the retinal mechanism we propose.